The relationship between carbonic anhydrase IX (CAIX) and patient survival in breast cancer: systematic review and meta-analysis - Suad A. K. Shamis; Joanne Edwards; Donald C. McMillan (BMC, 2023)
Abstract Purpose Hypoxia is a characteristic of many solid tumours and an adverse prognostic factor for cancer therapy. Hypoxia results in upregulation of carbonic anhydrase IX (CAIX) expression, a pH-regulating enzyme. Many human tissue studies have examined the prognostic value of CAIX expression in breast cancer but have yielded inconsistent results. Therefore, a systematic review and meta-analysis was undertaken to assess the prognostic value of CAIX expression for breast cancer patients. Methods The electronic databases were systematically searched to identify relevant papers. The clinical outcomes included disease-free survival (DFS), recurrence-free survival (RFS) and overall survival (OS) in breast cancer patients. Review Manager version 5.4 was employed to analysis data from 23 eligible studies (containing 8390 patients). Results High CAIX expression was associated with poorer RFS [HR = 1.42, 95% CI (1.32−1.51), p < 0.00001], DFS [HR = 1.64, 95% CI (1.34−2.00), p < 0.00001], and OS [HR = 1.48, 95% CI (1.22−1.80), p < 0.0001]. Heterogeneity was observed across the studies. There was an effect of the CAIX antibody employed, scoring methods, and tumour localisation on CAIX expression. Conclusion CAIX overexpression was significantly associated with poorer RFS, DFS, and OS in breast cancer patients. However, further work in high quantity tissue cohorts is required to define the optimal methodological approach.